Are Fiscal Multipliers Estimated with Proxy-SVARs Robust? - Giovanni Angelini; Giovanni Caggiano; Efrem Castelnuovo; Luca Fanelli (Center for Economic Studies and Ifo Institute (CESifo), 2020)
How large are government spending and tax multipliers? The fiscal proxy-SVAR literature provides heterogenous estimates, depending on which proxies - fiscal or non-fiscal - are used to identify fiscal shocks. We reconcile the existing estimates via a flexible vector autoregressive model that allows to achieve identification in presence of a number of structural shocks larger than that of the available instruments. Our two main findings are the following. First, the estimate of the tax multiplier is sensitive to the assumption of orthogonality between total factor productivity (non-fiscal proxy) and tax shocks. If this correlation is assumed to be zero, the tax multiplier is found to be around one. If such correlation is non-zero, as supported by our empirical evidence, we find a tax multiplier three times as large. Second, we find the spending multiplier to be robustly larger than one across different models that feature different sets of instruments. Our results are robust to the joint employment of different fiscal and non-fiscal instruments.
Keywords: C52; E62; 330; fiscal multipliers; fiscal policy; identification; instruments; structural vector autoregressions